2016
DOI: 10.5489/cuaj.3160
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on effects of pyrrolidine dithiocarbamate on ischemia-reperfusion injury in testis

Abstract: Introduction: The aim of this experimental study was to investigate the histopathological and biochemical effects of pyrrolidine dithiocarbamate, an antioxidant and inhibitor of NF-kβ, on ischemiareperfusion injury in rats. Methods: A total of 21 male Wistar-Albino rats were randomly distributed into three groups as sham group (Group 1), ischemia-reperfusion (I/R) group (Group 2) and I/R with pyrrolidine dithiocarbamate (PDTC) group (Group 3). Left testicles of rats in Groups 2 and 3 underwent testicular torsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Also, it has strong anti-inflammatory properties as it is a specific inhibitor of NFkB. 24,25,27 Thiol compounds such as N-acetyl-cysteine (NAC) or t-cysteine also inhibit NFkB activation. The basis of NFkB inhibition is the free oxygen radical scavenging effect of thiol groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it has strong anti-inflammatory properties as it is a specific inhibitor of NFkB. 24,25,27 Thiol compounds such as N-acetyl-cysteine (NAC) or t-cysteine also inhibit NFkB activation. The basis of NFkB inhibition is the free oxygen radical scavenging effect of thiol groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a potent antioxidant. [24][25][26][27] Studies have reported that PDTC protects and improves histopathology by reducing oxidative stress in organ damage caused by various agents. 25,28,29 To the best of our knowledge, no study has examined the protective effect of PDTC on testicular damage caused by MTX.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor kappa Β plays a crucial role in immune response, cellular proliferation, inflammatory, and apoptosis[ 117 ]. Pyrrolidine dithiocarbamate (PDTC) is a stable low-molecular thiol compound which acts by neutralizing ROS[ 118 ]. Kemahli et al[ 118 ] studied the antioxidant effect of PDTC in a TT model and found that administration of PDTC exaggerates the antioxidant system by lowering MDA levels, increasing SOD activity and improving Johnson scores of biopsy specimen.…”
Section: Searchmentioning
confidence: 99%
“…We used Johnsen’s score to evaluate the morphological damage of the seminiferous tubules [ 33 ]. When we checked the literature, we found that different research groups found significant decrease in Johnsen’s score of the testicular IR injury group compared to the control group [ 43 , 44 , 45 , 46 ]. In our study, there was a significant decrease of Johnsen’s score in IR group compared to Sham group as in other studies.…”
Section: ⧉ Discussionmentioning
confidence: 99%